Pengaruh Permainan Simak-Ulang-Ucap Terhadap Keterampilan Berbahasa Jawa Siswa Kelas I MI Ma'arif Tumenggungan Tahun Pelajaran 2023/2024 - Kunikmah, Arisma; Zuhdi, Ahmad; Fatiatun, Fatiatun (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2023)
The main objective of this research is to find out how to play the listen-repeat-say game and how it affects students’ mastery of Javanese language skills. This study used a quantitative approach with an experimental design of One-Group Pretest-Posttest Design. A before and after test was included in this design to measure the treatment applied. The samples in this study were 21 grade I students at MI Ma’arif Tumenggungan. The data obtained from this study prove that 1) The initial Javanese language skills of students which include speaking skills and writing skills obtained a percentage of 17% (not good enough) while listening skills and reading skills obtained a percentage of 33% (good enough). 2) The existence of the effect of the listen-repeat-say game on students’ Javanese language skills is evidenced by the results of hypothesis testing which obtained a Sig. (2-tailed) 0.000 <0.05. 3) Designing and describing the implementation of the listen-repeat-say game applied to Javanese.